2019
DOI: 10.1113/jp277443
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory pressure‐generating capacity is preserved during ventilatory and non‐ventilatory behaviours in young dystrophic mdx mice despite profound diaphragm muscle weakness

Abstract: Key points Respiratory muscle weakness is a major feature of Duchenne muscular dystrophy (DMD), yet little is known about the neural control of the respiratory muscles in DMD and animal models of dystrophic disease. Substantial diaphragm muscle weakness is apparent in young (8‐week‐old) mdx mice, although ventilatory capacity in response to maximum chemostimulation in conscious mice is preserved. Peak volume‐ and flow‐related measures during chemoactivation are equivalent in anaesthetized, vagotomized wild‐ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(83 citation statements)
references
References 55 publications
6
77
0
Order By: Relevance
“…Substantial diaphragm weakness in the mdx mice was confirmed by Burns et al . () but, surprisingly, it was demonstrated that (i) the ventilatory response to the combined hypercapnic hypoxia challenge was not significantly altered and (ii) there was no reduction in peak inspiratory pressure generation. In support of the former finding, a previous study Mosqueira et al .…”
Section: Main Findingsmentioning
confidence: 92%
See 4 more Smart Citations
“…Substantial diaphragm weakness in the mdx mice was confirmed by Burns et al . () but, surprisingly, it was demonstrated that (i) the ventilatory response to the combined hypercapnic hypoxia challenge was not significantly altered and (ii) there was no reduction in peak inspiratory pressure generation. In support of the former finding, a previous study Mosqueira et al .…”
Section: Main Findingsmentioning
confidence: 92%
“…To test the hypothesis that respiratory muscle weakness was associated with reduced inspiratory pressure generating capacity in mdx mice, Burns et al . () employed several ventilatory (e.g. O 2 and CO 2 challenges) and non‐ventilatory (e.g.…”
Section: Main Findingsmentioning
confidence: 99%
See 3 more Smart Citations